Healed. Womxn. Empowered.: creating healing spaces for women in places of conflict in Nyanga - Mbekeni, Kazeka Talisa (School of Architecture, Planning and Geomatics, 2021)
Gender-based violence (GBV) is a profound and widespread issue for women in South Africa, and this was demonstrated on the 4th of September, 2019 when womxn marched together to end GBV in South Africa after the death of local UCT student Uyinene "Nene" Mrwetyana. GBV is a significant obstacle for gender equality and female empowerment in South Africa and also has long-lasting psychological effects on the women who survive these events as well as those around them; altering the way they see themselves and others in relation to the world. There is a need for healing spaces for womxn in South Africa. Spaces that make women feel safe (physically and mentally) and empowered. The current healing spaces are mostly found in private clinics/hospitals patient-use (private space) and they are usually focused more on physical health (with the use of medicinal plants) but not centred around improving mental health. Retaining healing spaces in these sorts of environments (private spaces) makes them inaccessible. This project aims to contribute to the field of landscape architecture (and other space-makers) mainly focused on mental health and to encourage that these spaces be made more accessible, an essential part of our everyday lives, and implemented as a design solution for environments that could be detrimental to our mental health. This thesis carefully unpacks the issues around gender-based violence in South Africa (such as safety, representation and memorialization of local women, female empowerment, and mental health) and theories such as ecotherapy and ecopsychology to understand how the landscape can be used to provide a safe and healing environment for local women. Healing typically consists of cognitive restructuring (changing ideas around self-worth) and, in this study, it is explored at two levels. The one, empowerment is looked at more as a visual practice that takes place within the public realm whilst the other, inward-looking, self-discovery and meditative practice is looked at more as an experiential practice that takes place in the private realm. The chosen area of study is Nyanga (located in Cape Town, South Africa) which has been known to be the murder capital of South Africa. This area has also been identified as one of the top 30 GBV hotspots in South Africa with abuse and murder of women and children queer people in South Africa amongst the highest in the world. Zooming in on the Nyanga taxi Interchange precinct as the area that local women in Nyanga occupy most and unpacking the conditions of these used spaces and the key activities within this area which will inform the project and; majority-female informal trade taking place, the day clinic, the vegetable garden, and the under-utilized private land; to properly understand how these could be strategically integrated to create healing spaces for everyday use.